PENINGKATAN KOMPETENSI GURU MI MANARUL ISLAM MALANG MELALUI BEDAH BUKU “PROPHET MUHAMMAD: THE TEACHER” KARYA ABD AL-FATTAH ABU GHUDDAH - Fanani, Ahmad Daniyal; Haris, Abdul (Program Studi Pendidikan Agama Islam Tarbiyah IAI Muhammadiyah Bima, 2025)
This article discusses the motivation to become a beloved teacher by examining Abd al-Fattah Abu Ghuddah’s Prophet Muhammad: The Teacher. In Islamic education, a teacher is not merely a transmitter of knowledge but a model of virtue and character. The Prophet Muhammad exemplified the ideal educator through his actions, compassion, and adaptive teaching methods. His approach, grounded in exemplary conduct, kindness, and respect for individual differences, remains highly relevant today. The study reveals that when teachers emulate the Prophet’s methods, prioritizing patience, empathy, dialogue, and personal relationships, they inspire deep respect and affection from students. A practical implementation in an Islamic primary school showed a clear transformation: teachers shifted from traditional, rigid methods to a more humanistic, inclusive, and affectionate style. Thus, becoming a longed-for teacher is an attainable ideal, realized through the sincere internalization and practice of prophetic values. This research reaffirms that authentic presence, compassion, and character-building are the true foundations for lasting impact in the classroom.